1990
DOI: 10.1001/archderm.1990.01670300101017
|View full text |Cite
|
Sign up to set email alerts
|

CD8+ Cutaneous T-cell Lymphoma With Pagetoid Epidermotropism and Angiocentric and Angiodestructive Infiltration

Abstract: A 68-year-old woman had a peculiar clinical course of cutaneous lymphoma. She first developed nonpuritic erythematous macules with fine scales followed by development of erythematous infiltrated plaques. The clinical course could be interpreted as that of mycosis fungoides. Histologically, the lesions showed pagetoid infiltration of atypical lymphoid cells. Suddenly, with high fever, numerous purpuric, ulcerated, or crusted plaques with underlying infiltration or nodules began to appear on most areas of the pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
1
1

Year Published

1996
1996
2012
2012

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 12 publications
1
13
1
1
Order By: Relevance
“…31 However, none of our cases showed involvement of the oral cavity, palms, or soles, in contrast to cases described in prior reports. [31][32][33] Whether the activated cytotoxic phenotype contributes to the aggressive clinical behavior remains to be determined. Nevertheless, many different types of lymphoma can express cytotoxic molecules, including anaplastic large cell lymphoma, nasal NK/T-cell lymphoma, and SPTCL.…”
Section: Molecular Studiescontrasting
confidence: 91%
See 2 more Smart Citations
“…31 However, none of our cases showed involvement of the oral cavity, palms, or soles, in contrast to cases described in prior reports. [31][32][33] Whether the activated cytotoxic phenotype contributes to the aggressive clinical behavior remains to be determined. Nevertheless, many different types of lymphoma can express cytotoxic molecules, including anaplastic large cell lymphoma, nasal NK/T-cell lymphoma, and SPTCL.…”
Section: Molecular Studiescontrasting
confidence: 91%
“…In addition, lymphocytes in MF nearly always express CD4, a surface marker not present in ␥␦ CTCL. Interestingly, ␥␦ CTCLs share many common clinical and pathological features with epidermotropic suppressor/ cytotoxic CTCLs, [31][32][33][34] some of which have an ␣␤ phenotype. 31 However, none of our cases showed involvement of the oral cavity, palms, or soles, in contrast to cases described in prior reports.…”
Section: Molecular Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…This raises the question about the possibility of transition from one form (less aggressive) to another (more aggressive) within the CTCL. 25,26 On the other hand, the cases reported by Fujiwara et al, 7 Urrutia et al, 8 Agnarsson et al 9 in 1990, and Quarterman et al 10 in 1995 as being CD8 1 MF that behaved aggressively can be considered as true examples of primary cutaneous aggressive epidermotropic CD8 1 T-cell lymphoma because they presented by almost the same clinicopathological features of the first 8 cases described by Berti et al in 1999, 6 and so they were included in the literature review of the reported cases (Table I).…”
Section: Diagnostic Criteriamentioning
confidence: 98%
“…Die Prognose dieser Tumoren ist nicht einheitlich. Einerseits wird über rasch progrediente kutane Lymphome mit schlechter Prognose berichtet [1,5,10].Andererseits erwähnen manche Autoren günstigere Verläufe [1,8,9] mit lange anhaltenden kompletten Remissionen. Letztere weisen zum Teil eine Mykosis-fungoides-ähnliche Antigenstruktur auf (CD2-Positivität, CD7-Negativität).Aber es werden auch CD8-positive Varianten der Mykosis fungoides mit klinisch aggressiverem Verlauf beschrieben [4,10].…”
Section: Tumorstaging-untersuchungenunclassified